Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1016/j.conctc.2021.100763
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged exposure therapy for PTSD among spinal cord injury survivors: Study protocol for a randomized controlled trial

Abstract: The National Spinal Cord Injury Statistical Center estimates 294,000 people in the US live with a spinal cord injury (SCI), with approximately 17,810 new cases each year. Although the physical outcomes associated with SCI have been widely studied, the psychological consequences of sustaining a SCI remain largely unexplored. Scant research has focused on posttraumatic stress disorder (PTSD) in this population, despite prevalence estimates suggesting that up to 60% of individuals with SCI experience PTSD post-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 78 publications
1
3
0
Order By: Relevance
“…1 ). The improvement in symptoms was similar in magnitude to that seen in other trauma populations [ 40 ] and showed that this treatment approach is feasible in the inpatient rehabilitation setting [ 41 ]. Although feasible, we found that the standard 12-session PE treatment was difficult due to the nature of the inpatient rehabilitation setting, primarily the demanding schedule of physical, occupational, and other rehabilitative therapies.…”
Section: Introductionsupporting
confidence: 66%
See 3 more Smart Citations
“…1 ). The improvement in symptoms was similar in magnitude to that seen in other trauma populations [ 40 ] and showed that this treatment approach is feasible in the inpatient rehabilitation setting [ 41 ]. Although feasible, we found that the standard 12-session PE treatment was difficult due to the nature of the inpatient rehabilitation setting, primarily the demanding schedule of physical, occupational, and other rehabilitative therapies.…”
Section: Introductionsupporting
confidence: 66%
“…The interviewer rates participant responses to symptom questions on a 5-point scale of frequency and severity, from 0 (“Not at all”) to 4 (“6 or more times a week/severe”). This measure has been used in our ongoing studies [ 41 , [67] , [68] , [69] , [70] ] and will be conducted by a trained independent evaluator.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations